If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + x = 2x + -6 Reorder the terms: 3 + x = -6 + 2x Solving 3 + x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + x + -2x = -6 + 2x + -2x Combine like terms: x + -2x = -1x 3 + -1x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -1x = -6 + 0 3 + -1x = -6 Add '-3' to each side of the equation. 3 + -3 + -1x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = -6 + -3 -1x = -6 + -3 Combine like terms: -6 + -3 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9
| 200=8a | | r+12=41 | | -2*4+x=-48 | | x^2-4.8x+2=0 | | 27+x=135 | | 2y-12=-18 | | 7p=-49 | | 3(4r+5)+7=58 | | 3p+15=30 | | (2x+1)=56-(2x+1) | | 37x^2-3x+88=0 | | 55-x+28=17 | | x+2y+2z=70 | | 16x-3=9+5x | | x+2x=2x+30 | | 5m-(6w+9)=11 | | 7-3x=5x+19 | | 5p-7=4p+3 | | 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= |